Aplikasi Sistem Pakar Pendeteksi Gastroenteritis Berbasis Android - Misik Puspajati Nurmadjid Saputri; R. Rizal Isnanto; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2017)
Lack of public understanding of gastroenteritis, which is often suspected as diarrhea, causes the treatment of the disease to be less effective. An expert system application was developed to help people to detect gastroenteritis easily. The application used forward chaining method and best-first-search search algorithm. Expert knowledge was obtained from two doctors of the Gastroenterohepatology of Internal Medicine. The application runs on Android devices and has been able to detect gastroenteritis disease without dehydration, acute dehydration gastroenteritis mild, moderate and severe.